The Influence of Brand Image, Service Quality and Perceived Value on Brand Loyalty And Brand Equity Toyota Avanza - Ivan Armawan (Jurnal Indonesia Sosial Teknologi, 2021)
This type of research is a comparative causal research. This causal cooperative research aims to analyze the influence of the independent variable (independent) on the dependent variable. The study was conducted on Avanza car owners who service at the official Toyota repair shop, namely Auto2000 Balikpapan. The data collection technique used a questionnaire with a sample of 100 people. The research results were analyzed using the Amos application. The results showed that there was an influence of brand image, service quality and perceived value on brand loyalty and equity where the Toyota Avanza was able to provide good service so that the level of sales was increasing every year.